1987
DOI: 10.1093/jac/19.2.239
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy and safety of ceftizoxime, cefotaxime and latamoxef in the treatment of bacterial pneumonia in high risk patients

Abstract: One hundred and thirty-five patients with bacterial pneumonia who had risk factors (alcoholism, chronic obstructive pulmonary disease, corticosteroid therapy diabetes mellitus, advanced age, solid tumours) were randomly allocated in a double-blind fashion to receive either ceftizoxime (2-4 g every 8 h), cefotaxime (1-2 g every 4 h), or latamoxef (2-4 g every 8 h). Of the 84 patients evaluable for efficacy, clinical cure was achieved in 91%, 85%, and 89% of ceftizoxime- (20/22), cefotaxime-(23/27), and latamoxe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
1

Year Published

1988
1988
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
2
10
1
Order By: Relevance
“…The remaining 15 studies were included in the final meta-analysis. They were five RCTs [12,13,14,15,16], four prospective cohort studies [17,18,19,20], five retrospective cohort studies [21,22,23,24,25], and one case-control study [26], published between 1984 and 2016. A total of five NMTT-cephalosporins were included in the analysis; cefamandole [13,23,24], cefoperazone [20,22,25,26], cefotetan [15,16,18,19,20], cefmetazole [26], and moxalactam [12,14,17,21,22,24].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The remaining 15 studies were included in the final meta-analysis. They were five RCTs [12,13,14,15,16], four prospective cohort studies [17,18,19,20], five retrospective cohort studies [21,22,23,24,25], and one case-control study [26], published between 1984 and 2016. A total of five NMTT-cephalosporins were included in the analysis; cefamandole [13,23,24], cefoperazone [20,22,25,26], cefotetan [15,16,18,19,20], cefmetazole [26], and moxalactam [12,14,17,21,22,24].…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies (n = 9) [12,13,16,19,20,21,22,23,24] included in our review were conducted in the US, with the exception of four [14,17,18,25] that were conducted in England, one in South African [15], and one in Taiwan [26]. The studies reported that cephalosporins were prescribed for the following indications: pneumonia, preoperative and postoperative antibiotic regimen, and sepsis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations